Benthic indicators to use in Ecological Quality classification of Mediterranean soft bottom marine ecosystems, including a new Biotic Index - SIMBOURA, N.; ZENETOS, A. (Mediterranean Marine Science, 2002)
A general scheme for approaching the objective of Ecological Quality Status (EcoQ) classification of zoobenthic marine ecosystems is presented. A system based on soft bottom benthic indicator species and related habitat types is suggested to be used for testing the typological definition of a given water body in the Mediterranean. Benthic indices including the Shannon-Wiener diversity index and the species richness are re-evaluated for use in classification. Ranges of values and of ecological quality categories are given for the diversity and species richness in different habitat types. A new biotic index (BENTIX) is proposed based on the relative percentages of three ecological groups of species grouped according to their sensitivity or tolerance to disturbance factors and weighted proportionately to obtain a formula rendering a five step numerical scale of ecological quality classification. Its advantage against former biotic indices lies in the fact that it reduces the number of the ecological groups involved which makes it simpler and easier in its use. The Bentix index proposed is tested and validated with data from Greek and western Mediterranean ecosystems and examples are presented. Indicator species associated with specific habitat types and pollution indicator species, scored according to their degree of tolerance to pollution, are listed in a table. The Bentix index is compared and evaluated against the indices of diversity and species richness for use in classification. The advantages of the BENTIX index as a classification tool for ECoQ include independence from habitat type, sample size and taxonomic effort, high discriminative power and simplicity in its use which make it a robust, simple and effective tool for application in the Mediterranean Sea.